University of Malaya Online Vehicle Management System (OVMS) / Lee Lai Peng - Lee , Lai Peng (2002)
With the established of Internet technology, any computer can be linked from anywhere and anytime to gain the necessary information. Today, a huge number of the people connected to the Internet, and this inspire the creation of OVMs (Online Vehicle Management System) for University of Malaya. The current summon and transport registration System which handle by Pejabat Keselamatan is done by manually and outdated in this information world. Thus, the main Objectives of OVMS is to make the registration of transport easier and more convenient, to reduce administrative work for the Pejabat Keselamatan personnel, and to generate reports from the web-based system. Once the OVMS is developed, it is enable any authorized person to register their transport via this online system. It also ease the administrators works in maintaining the database. This system is targeted to be as simple as possible because most of the users for this system is non-technical users. The Waterfall Model with Prototyping methodology is chosen to develop this online system. Besides, development tools such as Active Server Pages (ASP). Microsoft Server SQL 7.0, and VB Script are used to develop the OVMS system.